Multinational business finance - Eiteman, David K. (Pearson, 2016)
For courses in International Finance. Authoritative, Comprehensive Coverage of Contemporary International Finance Renowned for its authoritative, comprehensive coverage of contemporary international finance, Multinational Business Finance trains the leaders of tomorrow's multinational enterprises to recognize and capitalize on the unique characteristics of global markets. Because the job of a manager is to make financial decisions that increase firm value, the authors have embedded real-world mini-cases throughout to apply chapter concepts to the types of situations managers of multinational firms face. The Fourteenth Edition , now with MyFinanceLab, attempts to capture the rapid evolution of our global marketplace, taking a closer look at the types of organizations that permeate the widespread arena, competition and opportunities in emerging markets, and how financial leadership can integrate the strategic and financial challenges that global businesses face today. MyFinanceLab® not included. Students, if MyFinanceLab is a recommended/mandatory component of the course, please ask your instructor for the correct ISBN and course ID. MyFinanceLab should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information. MyFinanceLab is an online homework, tutorial, and assessment product designed to personalize learning and improve results. With a wide range of interactive, engaging, and assignable activities, students are encouraged to actively learn and retain tough course concepts. Please note that the product you are purchasing does not include MyFinanceLab. MyFinanceLab Join over 11 million students benefiting from Pearson MyLabs. This title can be supported by MyfinanceLab, an online homework and tutorial system designed to test and build your understanding. Would you like to use the power of MyfinanceLab to accelerate your learning? You need both an access card and a course ID to access MyfinanceLab. These are the steps you need to take: 1. Make sure that your lecturer is already using the system Ask your lecturer before purchasing a MyLab product as you will need a course ID from them before you can gain access to the system. 2. Check whether an access card has been included with the book at a reduced cost If it has, it will be on the inside back cover of the book. 3. If you have a course ID but no access code, you can benefit from MyfinanceLab at a reduced price by purchasing a pack containing a copy of the book and an access code for MyfinanceLab (ISBN:9781292097985) 4. If your lecturer is using the MyLab and you would like to purchase the product... Go to www.myfinancelab.com to buy access to this interactive study programme. For educator access, contact your Pearson representative. To find out who your Pearson representative is, visit www.pearsoned.co.uk/replocator